Geological evaluation and gas bearing analysis for shale reservoir in Ziyun-Luodian typical area of southern Guizhou province, China - Wang, Keying; Cai, Ningbo; Du, Jiang; Gong, Shuhua; Li, Yan (Frontiers in Earth Science, 2022)
The Ziyun-Luodian area of southern Guizhou province in China is chosen as the research area and the Dawuba formation in Carboniferous system is the target stratum in this paper. Combined with laboratory experiments and mathematical analyses, geological evaluations on organic geochemistry, physical property of the reservoir, and gas bearing feature are all studied, and geological controls on gas occurrence are then analyzed. The following conclusions are achieved. The organic type is mainly II2 or III. TOC is generally in a range of 1-3 %, and Ro,max ranges from 1.7 to 4.4 %, with an average value of 2.4 %. Mineral compositions are mainly clay and quartz, with a few calcite and dolomite. The Specific surface area ranges from 6.6 to 29.8 m2/g, with an average value of 15.2 m2/g, and the pore volume varies from 0.012 to 0.046 cm3/g, with an average value of about 0.02 cm3/g. There is a strongly and positively linear relationship between specific surface area and pore volume. The porosity is mostly in the range of 1-3 %, with an average value of 1.8 %. Most of permeability is below 0.01 mD, with an average value of about 0.004 mD. There is an exponential and positive relationship between porosity and permeability. The gas content is generally below 2.0 m3/t. There are three obvious correlations for gas content versus buried depth ranges of 500-700 m, 700-1000 m, and 2700-3000 m. TOC influences gas content in a linear mode, and Ro,max influences gas content positively. The gas content has a positive relationship with clay mineral and a negative relationship with sapropelic percentage. The porosity and permeability are both positively correlated with gas content. The pore volume has a positive trend with gas content, and the specific surface area has a positively and strongly linear relationship with gas content.